Telling Ghost Stories Around a Bonfire—A Literature Review of Acute Bleeding Secondary to Pancreatitis - Gabriele Bellio; Silvia Fattori; Andrea Sozzi; Matteo Maria Cimino; Hayato Kurihara (Medicina)
Bleeding is a rare but serious complication of pancreatitis, significantly increasing morbidity and mortality. It can arise from various sources, including erosion of blood vessels by inflammatory processes, formation of pseudoaneurysms, and gastrointestinal bleeding. Early diagnosis and timely intervention are crucial for patient survival. Imaging modalities such as computed tomography and angiography are essential for identifying the bleeding source, where endoscopy may help in detecting and treating intraluminal hemorrhage. Management strategies for patients with extraluminal bleeding may involve angioembolization or surgical intervention, depending on the severity and location of the bleeding. While advances in diagnostic and therapeutic techniques have improved outcomes, bleeding in pancreatitis remains a challenging clinical problem requiring a multidisciplinary approach. This review aims to focus its attention specifically on the bleeding complications of pancreatitis.